Adherence to treatment in chronic kidney disease: Associations with therapeutic modalities and coping capacity - Meló, Cynthia De Freitas; Feijão, Georgia Maria Meló; Costa, Ícaro Moreira; Seidl, Eliane Maria Fleury; Ramos-Cerqueira, Ana Teresa De Abreu [UNESP]; De Arruda, Gabriel Huet Borges (FapUNIFESP (SciELO), 2024)
Objective hronic kidney disease treatment requires renal replacement therapy, with two possibilities - hemodialysis or peritoneal dialysis. Due to physical and psychosocial stressors, adherence to treatment becomes a challenge. Coping strategies play a mediating role between patients, health, and the disease. This study aimed to identify potential associations between the level of adherence to dialysis treatment, therapeutic modalities, and types of coping used. Method quantitative study was conducted with a non-probabilistic sample of 233 patients who responded to four instruments, analyzed through descriptive and inferential statistics. Results Were observed higher levels of adherence in attitudes towards social restrictions in peritoneal dialysis patients, and that both groups use different coping strategies. There are associations between confrontational and supportive coping and therapeutic adherence. Conclusion Subjects on peritoneal dialysis have a better attitude towards therapeutic adherence, highlighting the need for greater investment in this treatment.
Adesão ao tratamento na doença renal crônica: Associações com as modalidades terapêuticas e capacidade de enfrentamento
Keywords: Adaptation; Chronic; Psychological; Renal insufficiency; Treatment adherence and compliance